A importância da análise ambiental para as pequenas e médias empresas: um enfoque em planejamento estratégico empresarial - Mello, Alvaro Augusto Araújo (1980)
This essay 'THE IMPORTANCE OF fill ENVIROMENTAL ANALYSIS FOR THE SMAIl ANO MEDIUM SIZED COMPANIES: AN APPROACH IN STRATEGIC PLANNING', aims to demonstrate through a theorical and pragmatic outlook, organizational technology to be used by small and medium sized business. The theory of systems is used by means of the enviromental analysis.